Naphthoquinones: biological properties and synthesis of lawsone and derivates - a structured review - LÓPEZ LÓPEZ, Lluvia Itzel; NERY FLORES, Sendar Daniel; SILVA BELMARES, Sonia Yesenia; SÁENZ GALINDO, Aidé (Vitae, 2014)
Background: Naphthoquinones are natural pigments that are widely distributed in nature and have important biological activities. Lawsone (2-hydroxy-1,4-naphthoquinone) and its synthetic derivatives, and especially those containing nitrogen, have promising potential for the treatment of different diseases due to their antibacterial, antifungal, antiviral, antitumor and antiparasitic effects, and for pest control via their molluscicidal and insecticidal activities. Their pharmacological activities and mechanisms of action are related to their oxide/reduction and acid/base properties, and can be modulated by directly adding a substituted to the 1,4-naphthoquinone ring. Due to this, naphthoquinones and their derivatives are at the center of multiple areas of research. In this manuscript, we present a structured review of lawsone, a hydroxyl derivative of naphthoquinone, and discuss relevant reports about the chemistry and synthesis of derivatives. Finally, we present the pharmacological activities and mechanism of action reported. Objective: The purpose of this review is to present recent reports from the literature about the chemistry, synthesis and pharmacological properties of lawsone and its amine derivatives. Methods: This structured review presents a discussion about lawsone literature over the last ten years. The most representative studies including those about the chemistry of lawsone, the synthesis of its derivatives, and pharmacological properties were identified and selected. The information has been compiled, organized and presented into logical topics in order to provide a current review for the field of lawsone chemistry. Results: A general overview of the principal aspects of lawsone chemistry, the synthesis of its derivatives and their pharmacological activities and mechanism of action has been obtained. This provides researchers in the area with a framework from which to investigate further. Conclusions: Lawsone and its derivatives have promising potential for treating several diseases due to their antibacterial, antifungal, antiviral, antitumor and antiparasitic effects and have the potential to control pests via their molluscicidal and insecticidal properties. For this reason, it would be of interest to evaluate the synthetic derivatives of this compound for their pharmacologic actions; in the future, synthetic derivatives of lawsone could potentially be used to treat disease and be used as pesticides.